KREDIT BERMASALAH DALAM LIKUIDITAS DENGAN PERSPEKTIF CARACTER, CAPITAL, CAPASITY, COLLETERAL DAN CONDITION OF ECONOMIC (5C) (Studi Naratif pada PD.BPR Bank Gresik) - Kesa Ferdinand Pradana (Jurnal Manajerial, 2019)
This study aims to analyze the meaning of the relationship of problem loans with liquidity in the perspective of 5C in PD. BPR. Bank Gresik uses a narrative study approach. This study analyzes non-performing loans and liquidity with the perspectives of 5C (Character, Capital, Capacity, Colleteral and Condition of Economic. The results of the analysis show that non-performing loans are one of the causes of the decline in bank income or profits.